Global migration and Christian faith: implications for identity and mission / edited by M. Daniel Carroll R., Vincent E. Bacote - Carroll R., M. Daniel; Bacote, Vincent (Cascade Books, an imprint of Wipf & Stock Publishers, 2021)
"Human history is the history of migration. Never before, however, have the numbers of people on the move been so large nor the movement as global as it is today. How should Christians respond biblically, theologically, and missiologically to the myriad of daunting challenges triggered by this new worldwide reality? This volume brings together significant scholars from a variety of fields to offer fresh insights into how to engage migration. What makes this book especially unique is that the authors come from across Christian traditions, and from different backgrounds and experiences - each of whom makes an important contribution to current debates. How has the Christian church responded to migration in the past? How might the Bible orient our thinking? What new insights about God and faith surface with migration, and what new demands are placed now upon God's people in a world in so much need? Global Migration and Christian Faith points in the right direction to grapple with those questions and move forward in constructive ways." -- Back cover